Sales Range and Innovation Activity in the Industry System of Poland - Arkadiusz Swiadek (Institute of Economic Research (IER), 2017)
In the literature, there is a discussion on the importance of the spatial distans to the user in the context innovation activity. Although, most of this kind of studies concentrate on exporting enterprises and compare them to domestic ones. Exporting activity is very important for catching-up countries, because of technology transfer in its background. The aim of this paper is to determine whether the innovative activity in Poland's industrial system is a consequence of close interactions (local and regional), or perhaps conditioned by the imperative of functioning on the national and international market? Main hypothesis was to claim that on the current development level of Poland, the relationship between the range of sales and innovation activities are different from those in the more developed countries. Empirical studies was created in 2006-2012 as a result of the systematic collection of questionnaires filled by industry enterprises in Poland from all regions (5209 correct fulfilled questionnaires). Methodical analysis was based on the theory of probability - probit modeling, because dependent variables were binary (0 or 1). Local and regional environment is not conducive to stimulating innovation activity, but national spatial is a sufficient space, but high intensity observed only when the company has been working on the international market. It means, that the industry maturity level in Poland is good enough for creating a domestic innovation environment. This kind of an aggregation level should be stimulating by the government innovation policy.
Keywords: L52; O25; P51; O31; O32; O33; 330; innovation; industry; system; country; sale range